2020
DOI: 10.3389/fnagi.2020.00164
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Continuous Cervical Spinal Cord Stimulation Exerts Neuroprotective Effects in Experimental Parkinson’s Disease

Abstract: Background: Spinal cord stimulation (SCS) exerts neuroprotective effects in animal models of Parkinson's disease (PD). Conventional stimulation techniques entail limited stimulation time and restricted movement of animals, warranting the need for optimizing the SCS regimen to address the progressive nature of the disease and to improve its clinical translation to PD patients. Objective: Recognizing the limitations of conventional stimulation, we now investigated the effects of continuous SCS in freely moving p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 52 publications
(68 reference statements)
0
20
0
Order By: Relevance
“…In a recent study, small mobile devices for continuous SCS in freely moving parkinsonian rats were developed. [ 20 ] The research demonstrated both an effective delivery of SCS by a small mobile device and a time-dependency on neuroprotective effects of rats of the PD. Both groups of SCS treated rats typically had improved performance in both contralateral bias and methamphetamine rotation tests; however, the 24-hour stimulation group exhibited better therapeutic effects than the 8-hour stimulation group.…”
Section: Animal Models Of Spinal Cord Stimulationmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study, small mobile devices for continuous SCS in freely moving parkinsonian rats were developed. [ 20 ] The research demonstrated both an effective delivery of SCS by a small mobile device and a time-dependency on neuroprotective effects of rats of the PD. Both groups of SCS treated rats typically had improved performance in both contralateral bias and methamphetamine rotation tests; however, the 24-hour stimulation group exhibited better therapeutic effects than the 8-hour stimulation group.…”
Section: Animal Models Of Spinal Cord Stimulationmentioning
confidence: 99%
“…Such a system has already been demonstrated to be effective for DBS in PD animals and now a lightweight, continuous SCS mobile device has also been developed. [ 18 19 20 ] This method achieves minimum invasiveness, free movement with a wireless system, readily accessible adjustment of stimulation conditions, and robust, stable stimulation in PD animals for at least 2 weeks [ Figure 1 ]. Of note, Bluetooth signaling efficiently controlled stimulation parameters.…”
Section: Small Mobile Devices For Continuous Spinal Cord Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, both studies showed a positive effect in preserving the dopaminergic innervation of the striatum, reducing its loss by 30–35%. Recently, an investigation showed that continuous application of SCS (24 h ON SCS), starting immediately after injection of 6-OHDA, reduced the loss of dopaminergic neurons and their striatal projections by ~35% and ~32% respectively, while a regular SCS protocol (8 h SCS ON/16 h SVS OFF) counteracted the degeneration of the nigrostriatal dopaminergic pathway only by ~23% (Kuwahara et al, 2020 ). Thus, the periodicity of the treatment application reflects on different degrees of neuroprotection (Kuwahara et al, 2020 ).…”
Section: Electrical Neuromodulation Therapies For Pd and Hdmentioning
confidence: 99%
“…Recently, an investigation showed that continuous application of SCS (24 h ON SCS), starting immediately after injection of 6-OHDA, reduced the loss of dopaminergic neurons and their striatal projections by ~35% and ~32% respectively, while a regular SCS protocol (8 h SCS ON/16 h SVS OFF) counteracted the degeneration of the nigrostriatal dopaminergic pathway only by ~23% (Kuwahara et al, 2020 ). Thus, the periodicity of the treatment application reflects on different degrees of neuroprotection (Kuwahara et al, 2020 ). These data suggest that SCS could have a neuroprotective effect that might contribute to the relief of the observed motor symptoms in PD, given the relevance of dopaminergic projections in modulating the functioning of the circuit of the nuclei of the base through the regulation of cortical and subcortical neuronal activity during movement (Gerfen and Surmeier, 2011 ; Canessa et al, 2016 ).…”
Section: Electrical Neuromodulation Therapies For Pd and Hdmentioning
confidence: 99%